Effect of CO2, Nd : YAG, and ArF excimer lasers on dentin morphology and pulp chamber temperature: An in vitro study - TÜRKMEN, CAFER; GÜNDAY, MAHİR (LIPPINCOTT WILLIAMS & WILKINS, 2000)
This study compared the effect of three laser systems: CO2 (10.600 nm), Nd:YAG (1.064 nm), and ArF excimer (193 nm) Lasers on dentin hard tissue and on temperature increases of the pulp chamber. Sixty-six third molar teeth were used and randomly divided into three groups. A class I cavity was made to expose the dentin, and the pulp in the pulp chamber was removed via a hole bored in the cervical area. The pulp chamber was subsequently refilled with silicon grease, and a NiCr/NiSi thermocouple was inserted through the hole into the pulp chamber. The dentin surface was then lased for 30 s at the same settings (3 W, 2 mm spot size, 20 pps) with each laser. The average internal temperature increases were as follows: CO2, 37 degreesC; Nd: YAG, 28 degreesC; and ArF excimer, 1 degreesC. Scanning electron microscopy of the dentin in the occlusal cavity revealed extensive carbonization, isolated balls of recrystallized material, and the presence of smear layer at some dentinal tubule orifices for the CO2 and Nd:YAG lased teeth. Smear layer was also observed for the ArF excimer samples; however, they exhibited far less surface cavities than the others and seemed to undergo little morphological change on the dentin.
Keywords: IN-VITRO; ENAMEL; RADIATION